Loss of galectin‐3 decreases the number of immune cells in the subventricular zone and restores proliferation in a viral model of multiple sclerosis. Issue 1 (4th September 2015) - James, Rachel E.; Hillis, James; Adorján, István; Gration, Betty; Mundim, Mayara V.; Iqbal, Asif J.; Majumdar, Moon‐Moon; Yates, Richard L.; Richards, Maureen M. H.; Goings, Gwendolyn E.; DeLuca, Gabriele C.; Greaves, David R.; et al.
Abstract : Multiple sclerosis (MS) frequently starts near the lateral ventricles, which are lined by subventricular zone (SVZ) progenitor cells that can migrate to lesions and contribute to repair. Because MS‐induced inflammation may decrease SVZ proliferation and thus limit repair, we studied the role of galectin‐3 (Gal‐3), a proinflammatory protein. Gal‐3 expression was increased in periventricular regions of human MS in post‐mortem brain samples and was also upregulated in periventricular regions in a murine MS model, Theiler's murine encephalomyelitis virus (TMEV) infection. Whereas TMEV increased SVZ chemokine (CCL2, CCL5, CCL, and CXCL10) expression in wild type (WT) mice, this was inhibited in Gal‐3 −/− mice. Though numerous CD45+ immune cells entered the SVZ of WT mice after TMEV infection, their numbers were significantly diminished in Gal‐3 −/− mice. TMEV also reduced neuroblast and proliferative SVZ cell numbers in WT mice but this was restored in Gal‐3 −/− mice and was correlated with increased numbers of doublecortin+ neuroblasts in the corpus callosum. In summary, our data showed that loss of Gal‐3 blocked chemokine increases after TMEV, reduced immune cell migration into the SVZ, reestablished SVZ proliferation and increased the number of progenitors in the corpus callosum. These results suggest Gal‐3 plays a central role in modulating the SVZ neurogenic niche's response to this model of MS. GLIA 2016;64:105–121 Main Points: Gal‐3 is increased in MS. Gal‐3 is necessary for chemokine increases in MS model. Loss of Gal‐3 reduces number of immune cells in SVZ.